2016
DOI: 10.1186/s12944-016-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating oxidative stress, serological- and haematological status of dogs suffering from osteoarthritis, after supplementing their diet with fish or corn oil

Abstract: BackgroundOxidative stress plays an important role in the pathogenesis of disease, and the antioxidant physiological effect of omega-3 from fish oil may lead to improvement of canine spontaneous osteoarthritis (OA).MethodsIn this prospective randomized, controlled, double-blinded study, we assessed haematological and biochemical parameters in dogs with OA following supplementation with either a concentrated omega-3 deep sea fish oil product or corn oil. Blood samples from 77 client-owned dogs diagnosed as havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 99 publications
(143 reference statements)
1
17
2
Order By: Relevance
“…Recent in vivo studies have shown that treating osteoarthritic dogs with n‐6‐rich corn oil led to the attenuation of oxidative stress markers in the blood. The improvement was almost comparable to dogs receiving fish oil (Barrouin‐Melo et al., ). This is the first study to show that not only EPA but also n‐6 fatty acids may be beneficial in inflammatory diseases.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Recent in vivo studies have shown that treating osteoarthritic dogs with n‐6‐rich corn oil led to the attenuation of oxidative stress markers in the blood. The improvement was almost comparable to dogs receiving fish oil (Barrouin‐Melo et al., ). This is the first study to show that not only EPA but also n‐6 fatty acids may be beneficial in inflammatory diseases.…”
Section: Discussionsupporting
confidence: 56%
“…It is known that chondrocytes have only limited access to nutrients due to the avascular, dense and negatively charged matrix (Villalvilla, Gómez, Largo, & Herrero‐Beaumont, ). However, feeding studies provide evidence that diets rich in n‐3 fatty acids alter the fatty acid composition in canine serum (Barrouin‐Melo et al., ; Hall, Picton, Skinner, Jewell, & Wander, ; Mehler et al., ) and that fatty acids are generally transported to the joints bound to albumin or lipoproteins (Arkill & Winlove, ). To mimic the process of fatty acid transport, we included 5% of FCS in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a major actor in skin aging process (Rinnerthaler et al, 2015), therefore, the identification of antioxidant properties is of high interest for the development of antiaging cosmetics. To demonstrate the ability of our method to reveal antioxidant effects, we chose two known antioxidant oils: olive and corn oil (Barrouin-Melo et al, 2016;Carnevale et al, 2018). Both were able to decrease the ROS overproduction induced by an oxidant agent.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant positive controls, olive oil and corn oil (Sigma-Aldrich, France), were selected according to the literature (Cheung et al, 2007;Barrouin-Melo et al, 2016;Carnevale et al, 2018).…”
Section: Antioxidant Effectsmentioning
confidence: 99%
See 1 more Smart Citation